M&A Performance and Economic Impact: Integration and Critical Assessment of Methodological Approach - Andriuskevicius, Karolis (Vysoké učení technické v Brně, Fakulta podnikatelská, 2017)
Purpose of the article is to investigate and critically discuss existing methodologies employed within the M&A performance framework. Methodology/methods: The research has been carried out as a structured assessment of past literature. The findings from scientific articles and studies by various scholars have been categorized, grouped and summarized to discern a meta‐analytic view of the work carried out to date. Scientific aim is to ascertain and evaluate theoretically existing methodologies used in empirical studies that would allow proper and critical understanding of the results of various findings in the holistic and global M&As area. Findings: The research elaborates on several key developments in M&A methodology and performance studies carried out in empirical works during the last two decades. The findings help to independently and objectively assess performance of M&A from a holistic perspective. Conclusions: Each methodology measuring either M&A performance on a corporate level or effects of M&A on the economy level shall be interpreted and relied on with caution as each of them dispose their limitations whereas application of these methodologies is subject to data availability and case specific.
Keywords: M&A; methodology; M&A performance; event study; accounting study; case study; strategic management; trends; economic growth